How the provision of childcare affects attitudes towards maternal employment - Anja Roth (Swiss Journal of Economics and Statistics, 2020)
Do childcare institutions affect gender norms of individuals? I examine the introduction of childcare services and their impact on voters' support of policies promoting maternal employment. I address the inherent endogeneity between institutions and attitudes by exploiting regional variation in the regulations and provision of childcare for school children outside of regular school hours. My results show that the expansion of childcare for school children increases voters' support of policies promoting maternal employment. This indicates a direct effect of local institutions on voters' attitudes. I additionally show that as public costs of the new facilities increase, support of additional policies promoting maternal employment decreases.
Keywords: H23; H31; J13; J18; 330; Childcare; Gender norms; Maternal employment; Policy evaluation